Immunohistochemical Expression of Cyclin D1, Cytokeratin 20, and Uroplakin III in Proliferative Urinary Bladder Lesions Induced by o-Nitroanisole in Fischer 344/N Rats. (May 2016) - Willson, C. J.; Flake, G. P.; Sills, R. C.; Kissling, G. E.; Cesta, M. F.
O -Nitroanisole is an intermediate in the manufacture of azo dyes. In a National Toxicology Program stop-exposure study, o -nitroanisole induced hyperplasia, papillomas, and papillary carcinomas in the urinary bladder of Fischer 344/N rats. o -Nitroanisole was investigated since occupational or environmental exposure to aniline and azo dyes is a risk factor for urinary bladder cancer in humans. The current study describes the morphology of urinary bladder neoplasms seen in rats with respect to those observed in humans. This study also evaluated immunohistochemical expression of the cell cycle–related proteins cyclin D1 and p53 and the differentiation markers cytokeratin 20 and uroplakin III in hyperplastic ( n = 11) and neoplastic ( n = 6 papillomas, n = 11 carcinomas) lesions of the urinary bladder epithelium from rats treated with o -nitroanisole and in normal ( n = 6) urinary bladders from untreated rats. The tumors observed were more similar to the papillary type rather than the muscle-invasive type of urinary bladder cancer in humans. The preneoplastic and neoplastic lesions observed suggest progression from hyperplasia to papilloma to papillary carcinoma. With neoplastic progression (hyperplasia to papilloma to carcinoma), cyclin D1 immunoreactivity progressively increased in intensity, percentage of cells staining, and distribution. Overexpression of p53 was not found. Cytokeratin 20 staining decreased in superficial cells, while uroplakin III staining increased in intermediate and basal cells with progression from hyperplasia to carcinoma. The results are consistent with increased cell cycle dysregulation or proliferation (cyclin D1), decreased differentiation (cytokeratin 20), and abnormal differentiation (uroplakin III) as lesions progress toward malignancy.